A Review of Light Reflection and Transmission Methods in Monitoring Non-Aqueous Phase Liquid Migration in Porous Media - Alazaiza, M. Y. D.; Ngien, S. K.; Wan Faizal, Wan Ishak; Samira, A. Kamaruddin (Asian Research Publishing Network, 2016)
Recently, image analysis techniques in monitoring non-aqueous phase liquid (NAPL) migration have been gaining attention from researchers. Over the last two decades, photographic methods such as light reflection and light transmission methods have been shown to be applicable and effective tools for characterization and measuring NAPL migration. A review of recent studies published on light reflection and light transmission methods used in NAPL migration is summarized and presented in this paper. Besides discussion on the research efforts, recommendations for future research in using light reflection and light transmission methods are provided. This study concluded that, although having some limitations and drawbacks, photographic methods are still a promising and valuable tool for measuring NAPL migration.